2007
DOI: 10.2214/ajr.05.2048
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Lighting: Effect of Illumination on Soft-Copy Viewing of Radiographs of the Wrist

Abstract: Typical office lighting and current recommendations on ambient lighting can reduce diagnostic efficacy compared with lower levels of ambient lighting. If, however, no light other than that of the monitor is used, results are similar to those with excessive levels of lighting. Careful control of ambient lighting is therefore required to ensure that diagnostic accuracy is maximized, particularly for clinicians not expert in interpreting posteroanterior wrist images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 11 publications
0
61
0
1
Order By: Relevance
“…The study results, however, support and advance findings from previous studies that suggested an increase of ambient lighting will not degrade detection performance. Several studies using both simulated images and clinical radiographs have shown that moderate levels of ambient lighting (40-50 lx) should not degrade, and may improve, observer detection performance [5,8,9,25]. In contrast to the current study, however, the previous studies utilized observers who either had no radiology reading experience or were accustomed to reading images under elevated ambient lighting levels.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The study results, however, support and advance findings from previous studies that suggested an increase of ambient lighting will not degrade detection performance. Several studies using both simulated images and clinical radiographs have shown that moderate levels of ambient lighting (40-50 lx) should not degrade, and may improve, observer detection performance [5,8,9,25]. In contrast to the current study, however, the previous studies utilized observers who either had no radiology reading experience or were accustomed to reading images under elevated ambient lighting levels.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast to film and CRTs, modern calibration-capable LCDs, with intrinsically low diffuse reflection coefficients and high luminance ratios may permit a moderate increase of ambient lighting without image quality degradation [7]. Following this assumption, theoretical, and psychophysical studies have provided preliminary evidence that radiologist performance should not degrade, and may improve, under a controlled ambient lighting increase [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Images were viewed on a dedicated image review station (DS3000, Agfa), which was calibrated for each reading session to DICOM Part 4 Curve standard. Ambient lighting conditions in the viewing room were maintained throughout the study at 25-40 lx [16].…”
Section: Discussionmentioning
confidence: 99%
“…For other modalities, the FDA does not restrict the use of compression, but it does require manufacturers of devices that use irreversible compression to submit data on the impact of the compression on quantitative metrics of image quality (such as peak signalto-noise ratio) [3]. Since it is known that such simple metrics do not correlate well with human observer assessment of quality or performance for diagnostic tasks [5], the claim of the manufacturer that irreversible compression is satisfactory may not be sufficient and the burden remains on the responsible physician to assure that the image quality is sufficient to achieve a diagnostically acceptable goal.…”
Section: Compressionmentioning
confidence: 99%
“…2. Viewing conditions should be optimized to minimize eye fatigue by controlling reading room lighting to eliminate reflections on the monitor and lowering the ambient lighting level as much as is feasible without turning the lighting off completely (20-40 lx is recommended in the work space environment) [5]. Brighter ambient lighting may be tolerable or even desirable so long as conformance with AAPM Task Group 18 specifications is maintained.…”
Section: Displaymentioning
confidence: 99%